2013
DOI: 10.1038/gim.2012.175
|View full text |Cite
|
Sign up to set email alerts
|

Cascade carrier testing after a child is diagnosed with cystic fibrosis through newborn screening: investigating why most relatives do not have testing

Abstract: Original research article INTRODUCTIONNewborn screening (NBS) for cystic fibrosis (CF) has increasingly been adopted by many countries worldwide, including Australia and New Zealand (since 1981), the United Kingdom (2007), a number of other countries and regions in Europe, and the United States. [1][2][3] The birth prevalence of CF is ~1 in 3,500 for northern European populations, 4 with a carrier frequency of 1 in 25, making it the most common severe recessive condition in children. In the state of Victoria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Further, while probands frequently describe feeling a sense of obligation about informing other at-risk relatives [7], they may be reluctant to do so due to existing challenging family dynamics and relationships [8,9]. Finally, probands may wish to protect their family members from anxiety [10-13] or they may be experiencing difficulties in coming to terms with their own diagnosis, [1,14] making communication problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Further, while probands frequently describe feeling a sense of obligation about informing other at-risk relatives [7], they may be reluctant to do so due to existing challenging family dynamics and relationships [8,9]. Finally, probands may wish to protect their family members from anxiety [10-13] or they may be experiencing difficulties in coming to terms with their own diagnosis, [1,14] making communication problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the reasons for not testing in relatives of 30 CF children diagnosed through newborn screening, McClaren et al [33] recently showed that the main reasons mentioned by relatives are irrelevant perception of the test's usefulness, lack of awareness of the possibility to do the test and test considered as something to do later.…”
Section: Discussionmentioning
confidence: 98%
“…Communication should certainly be easier since set up of NBS programs and multidisciplinary disease management in CF centers. The need to provide support to parents to facilitate the information transmission appears crucial [33]. Recent changes in French laws that now allow GPs to inform relatives of CF patients might have an impact on the uptake rate of testing in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are likely multifactorial, including insufficient referrals to clinical genetics, variable reporting of relatives by probands, inadequate understanding and communication of tests, feelings of irrelevance and deferring the process by relatives. [100][101][102] The use of screening has been investigated. The risk of ovarian cancer algorithm (ROCA) using serum CA125 and transvaginal ultrasound has been proposed for high-risk women; however, impact on survival is not known.…”
Section: Interventions For Women Carrying a Pathogenic Variantmentioning
confidence: 99%
“…Uptake of cascade testing in this situation has been noted to be relatively low, estimated at 15% to 57% in one systematic review and genetic testing in eligible women with ovarian cancer also low. The reasons for this are likely multifactorial, including insufficient referrals to clinical genetics, variable reporting of relatives by probands, inadequate understanding and communication of tests, feelings of irrelevance and deferring the process by relatives . The use of screening has been investigated.…”
Section: Introductionmentioning
confidence: 99%